Bolinger's meaning and form as a pragmatic filler in Chomskyan X-Bar module. - Ali, Amjad; Iqbal, Muhammad (Journal of Humanities & Social Sciences (Pakistan), 2020)
X-bar module characterizes the syntactic configuration of phrase constituents and recommends various tests for determining their syntactic presentations. The theory, however, does not account for plausible semantic and pragmatic implications of the constituents. The theory suffers a few inaccuracies in its overemphasis on syntactic dimensions of the constituents and its assignment of peripheral significance to their semantic and pragmatic considerations. This paper is an attempt in theoretical linguistics to fill these potential loopholes by applying the theoretical model of Meaning and Form. The study is delimited in its focus because it discusses two aspects of X'-module. The first half discusses the notions of complement and adjuncts while the second part brings into focus the genitive dimension of POSS-NPs. Besides semantic and pragmatic dimensions, the study analyzes genitive structures within the framework of DP-Hypothesis. The study has used Meaning and Form model as a theoretical tool for plugging in the gaps and has sought the support of other linguists whose notions are at par with the model and whose views can be cited as potential semantic and pragmatic fillers in the module. The study follows a cross-linguistic approach and examines the syntactic configuration of the module in Pashto language. This has been done to highlight the validity of this module across languages.